Antimicrobial Activity and Chemical Composition of the Essential Oil from Campanula glomerata L. Subsp. Hispida (Witasek) Hayek - Sinek, Kadriye; Yilmaz Iskender, Nagihan; Yayli, Busra; Alpay Karaoglu, Sengul; Yayli, Nurettin (Asian Journal of Chemistry, 2011)
The volatile components of the essential oil from Campanula glomerata L. subsp. hispida (Witasek) Hayek was analyzed by GC and GC-MS. Forty-eight compounds representing 89.0 % of the total oil were characterized and the main constituents of this specie were found to be hexadecanoic acid (24.51 %), docosane (15.9 %), isocitronellene (12.6 %), heneicosane (4.6 %), hexahydrofarnesyl acetone (3.2 %), 9-tricosene (1.6 %), octadecanol (1.4 %), caryophyllene oxide (1.3 %), a-funebrene (1.2 %), b-thujaplicinol (1.1 %), pentadecanoic acid (1.1 %), tricosane (1.1 %), (2E,4E)-decadienal (1.0 %), (E)-b-damascenone (1.0 %) and (E)-caryophyllene (1.0 %). The antimicrobial activity of the isolated essential oil of the plant was also investigated and it showed moderate antimicrobial and antifungal activities against Pseudomonas aeruginosa, Staphylococcus aureus, Enterococcus faecalis, Bacillus cereus, Mycobacterium smegmatis, Candida albicans and Saccharomyces cerevisiae.